Clinical competence in nursing education: a concept analysis (Media Penelitian dan Pengembangan Kesehatan, 2026)
Introduction: Clinical competence is a fundamental component of nursing education; however, the concept remains inconsistently defined across contexts. This lack of clarity hampers effective teaching, assessment, and the development of shared competency standards. Objective: This study aimed to clarify the construct of clinical competence for prelicensure nursing students during clinical education and to identify its implications for the learning process and evaluation. Methods: This study employed Walker and Avant’s concept analysis systematically following the sequential steps of concept selection, multidisciplinary literature exploration, and identification of defining attributes, antecedents, and consequences. A literature review was conducted using Scopus, Proquest, Springer, and SAGE Journal. Searches conducted from January 2018-December 2023 identified 70 records, of which 18 studies met the inclusion criteria. The analysed literature encompassed multiple health-related disciplines, including nursing, digital health, medicine, midwifery, dentistry, allied health, physical therapy, and obstetrics. Results: Clinical competence is conceptualised as an integrative capability encompassing cognitive, affective, and psychomotor domains, strengthened by advanced nursing skills, soft skills, leadership, and professionalism. These capabilities develop through formal education and supervised clinical experiences and are influenced by both educational contexts and individual factors. Clinically competent students can deliver safe, effective, high-quality care, maintain nursing standards, and perform efficiently in professional settings. Conclusion: This study provides a refined operational definition and key attributes of clinical competence, offering guidance for curriculum development, instructional strategies, and assessment practices in competency-based nursing education. The findings highlight the importance of standardised definitions to improve teaching quality and consistency in evaluating clinical competence